2012
DOI: 10.1021/mp300075u
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Wound Healing Activity of Curcumin Loaded Oleic Acid Based Polymeric Bandage in a Rat Model

Abstract: Wound healing is an intricate multistage process that includes inflammation, cell proliferation, matrix deposition and remodeling phases. It is often associated with oxidative stress and consequent prolonged inflammation, resulting in impaired wound healing. Curcumin has been reported to improve wound healing in different animal models. In order to increase the efficacy of curcumin in the healing arena a curcumin loaded oleic acid based polymeric (COP) bandage was formulated. The in vivo wound healing potency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
136
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(153 citation statements)
references
References 41 publications
8
136
0
4
Order By: Relevance
“…A transcription factor NFκB, that modulates many genes which are suspected in the commencement of inflammatory responses can be inhibited equally with the help of curcumin. This transcription factor is provoked by numerous kinases (Protein kinase B (PKB), phosphoinositide 3-kinase (PI3K), I kappa B kinase (IKK)) and curcumin disturbs a variety of the pathways occurred in this event [44]. The down regulation of the assertion of P13K and Protein kinase B (PKB/AKT kinases) are also shown which in turn leads to reduced activation of the NFκB gene and decreases inflammation.…”
Section: Curcumin As Anti-inflammatorymentioning
confidence: 99%
See 3 more Smart Citations
“…A transcription factor NFκB, that modulates many genes which are suspected in the commencement of inflammatory responses can be inhibited equally with the help of curcumin. This transcription factor is provoked by numerous kinases (Protein kinase B (PKB), phosphoinositide 3-kinase (PI3K), I kappa B kinase (IKK)) and curcumin disturbs a variety of the pathways occurred in this event [44]. The down regulation of the assertion of P13K and Protein kinase B (PKB/AKT kinases) are also shown which in turn leads to reduced activation of the NFκB gene and decreases inflammation.…”
Section: Curcumin As Anti-inflammatorymentioning
confidence: 99%
“…It was noticed that the prohibition of NFκB pathway is due to the up regulation in IκB-α protein. Hence, Mohanty et al [44] revealed that curcumin decreases inflammation at wound sites caused by the stimulation of the NFκB pathway. Conflicting to Mohanty's conclusion, an in vivo study of Kulac et al reported an increase in inflammatory cell infiltration to burn wounds on rats in curcumintreated groups compared to untreated groups [45].…”
Section: Curcumin As Anti-inflammatorymentioning
confidence: 99%
See 2 more Smart Citations
“…46 Furthermore, it induces down-regulation of NFκB pathway to inhibit the oxidative damage in human keratinocytes and fibroblasts. 47 However, the hydrophobicity of Cur has limited its use in clinical practice. 48 And nanotechnology has been widely used to improve the water solubility of hydrophobic drugs through encapsulation in polymer micelles, NPs, and liposomes.…”
mentioning
confidence: 99%